(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Attenuation due to rain predictive models have been used to calculate the impact of rainfall on satellite communication for six stations in Malaysia. The impact of rainfall is very important for designing a modern satellite system for heavy rainfall climatic regions like Malaysia, with large annual rainfall accumulation exceeding 3000 mm and rainfall rate exceeding 150 mm/h at Ku (12/14 GHz), Ka (20/30 GHz) and V (40/50 GHz) bands. The present result shows that the avalibility of link for 99.99% at the three bands for uplink and downlink to Malaysian Communication Satellite (MEASAT-3a) is not practicable. The results suggest link availability of 99.9% for Ku-uplink and Ka downlink, while 99% for Ka uplink and 99% for V band uplink and downlink due to high annual rainfall rates for most of the stations. The overall result shows that the impact of heavy rainfall on satellite communication will be more severe in the Eastern part than the Western of Malaysia.